Development of an OspC vaccine against lyme borreliosis - Livey, I... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
Outer-surface protein C (OspC) is a plasmid-encoded lipoprotein and protective antigen produced by Lyme disease borrelia species. OspC is potentially valuable as a vaccine component, but due to the high degree of antigenic heterogeneity of OspC, an OspC-based vaccine has to contain several antigenic forms of OspC. The production of a multivalent OspC vaccine using antigen expressed in borrelia burgdorferi sensu lato is associated with many technical and economical disadvantages. Consequently, we have chosen to produce OspC in Pichia pastoris and to assess the ability of this recombinant OspC to induce antibody production and protective immunity. Mice were immunized with recombinant OspC combined with AI(OH)3 and the antibody (IgG) response to OspC and the resistance of the immunized mice to infection with virulent borrelia afzelii were evaluated. OspC produced in Pichia pastoris is highly immunogenic and protective when adsorbed to AI(OH)3, an adjuvant that is acceptable for use in humans. Recombinant OspC derived from Pichia pastoris can be prepared in a form that is suitable for use in an OspC-based vaccine against Lyme borreliosis.
Keywords: Borrelia burgdorferi; Disease models, animal; Dna mutational analysis; Genetics; Lyme disease; Mice; Prevention and control; Vaccines, synthetic